Climate services for smallholder farmers: helping farmers cope with risk - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Through the ages, farmers have used indigenous knowledge and traditional coping strategies to adapt to changes in weather and climatic conditions. Now, increasingly erratic climate variability is making it difficult for farmers to keep up. Climate uncertainty often influences farmers’ decisions. It may deter them from adopting new technologies and market opportunities. While taking such risks could improve yields and boost profits in a good season, an extreme weather event or outbreak of disease can wipe out crops or livestock, leaving farmers with nothing to eat and a large debt to repay. Institutions that influence and support farmers, such as national agricultural research and extension systems and development non-governmental organizations (NGOs), are also affected by climate uncertainty because it affects the type of backup that they provide to farmers. Climate uncertainty also has a negative impact on the providers of credit and markets for productive inputs and can make it difficult for smallholder farmers to benefit from agricultural markets. Climate information reduces uncertainty and can help farmers make better use of new seeds and technologies. Such information can be used to support complex and context-specific decisions about farm labour and resource allocation. Climate information should be accompanied by services that communicate, train and help users understand how to interpret and act on the information.